Nigella sativa supplementation attenuates recognition memory and cellular morphometric impairments induced by toluene administration in mice - Nur Lisa Mohd Yusoff; Durriyyah Sharifah Hasan Adli; Yin, Sheena Xin Tiong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Toluene exposure has been associated with detrimental effects on the central nervous system. Discovering natural products that can offer neuroprotection following toluene exposure is an essential alternative. Nigella sativa (NS), a popular natural supplement, is a good candidate due to its antioxidant and neuroprotective properties. The study aimed to investigate the protective potentials of NS against toluene, on recognition memory performance in the Novel Object Recognition (NOR) test and cellular morphometric measurements of hippocampal CA1 pyramidal neurons. Adult male ICR mice (n30) were randomly divided into five groups; G1: corn oil (CO), G2: toluene (TOL), G3: toluene and NS seed suspension (TOL-NSS), G4: toluene and NS oil (TOL-NSO), G5: toluene and thymoquinone (TOL-TQ). NS supplementations were administered orally once daily for 14 consecutive days while 500 mg/kg b.w. toluene was administered intraperitoneally from day 8 until day 14. Behavioural NOR test was conducted. Subsequently, mice were intracardially perfused and the brains were dissected, then histologically processed. The somatic size and shape of hippocampal CA1 pyramidal neurons were quantified according to specific morphometric parameters. Toluene reduced recognition memory performance of mice and somatic size of hippocampal CA1 pyramidal neurons. Contradictorily, TQ, NSO, and NSS improved mice recognition memory and somatic size of hippocampal CA1 pyramidal neurons. Somatic shape of hippocampal CA1 pyramidal neurons was unaffected by the different treatments. Although nonsignificant differences were observed, the results indicated the tendency for toluene to cause impairment, while NS supplementations improved mouse recognition memory performance and hippocampal neuronal neuron structure.